The study of role of mammography and fine needle aspiration cytology in the diagnosis of early breast carcinoma - Stephen, Biju; V. V., Manoj (International Surgery Journal, 2021)
Background: Epidemiologically breast cancer is the most common form of cancer among women. Prevalence rate of breast cancer is higher in urban women of middle age group. Early diagnosis of breast carcinoma is required for effective treatment else it may lead to mortality if advanced to stage 3 or 4. At present, there are different diagnosis modalities for early stage breast carcinoma. Currently triple diagnostic assessment including clinical, radiological and pathological examinations with 99% sensitivity is used in diagnosing all palpable breast lumps. The aim of the study was to determine the sensitivity and specificity of mammogram and Fine needle aspiration cytology (FNAC) in diagnosing breast cancer. Methods: A cross sectional study was conducted on total 80 female patients above 30 years of age with a palpable breast lump. Patients were sent for mammography, fine needle aspiration cytology and histopathological examinations. Results of mammography, FNAC and HPR were compared and statistically correlated. Results: Sensitivity of mammogram diagnosis was observed to be 92.857%, specificity as 86.842%, positive and negative predictive values to be 88.636% and 91.667% respectively. Therefore, current study findings revealed accuracy of mammogram to be 90.000%. Sensitivity of FNAC diagnosis was observed to be 92.857% and specificity to be 100%, positive and negative predictive values were observed to be 100% and 92.683% respectively. The study results revealed that FNAC diagnosis exhibited accuracy of 96.250%. Conclusions: Current investigation findings revealed that FNAC has more accuracy in predicting breast cancer than mammogram. Also, it was concluded that there is a significant association between FNAC and mammogram diagnosis.